The Effect of Self-Management Practice and Non-Physical Work Environment on Work Productivity in PT. Central Mega Kencana (Frank & Co) - Gunawan, Teddy; Budiawan, Andi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
This study aims to explore the impact of self-management practices and work environments to support the increase in the productivity of individual workers and teams and even productivity in quality and quantity. The methodology of this study is based on survey data from 182 workers at PT Central Mega Kencana (Frank & Co). The analysis used to test the dimensions of self-management practice and work environment in work productivity is multiple regression analysis with the help of the SPSS 25 data processing system. The results of this study show that self-management practice and work environment affect the work productivity of PT. Central Mega Kencana (Frank&Co). The magnitude of the influence of self-management practices and work environments on employee work productivity was 35.3%.